A Mini-Review on Applications of 3D Printing for Microbial Electrochemical Technologies - Chung, Tae Hyun; Dhar, Bipro Ranjan (Frontiers in Energy Research, 2021)
For the past two decades, many successful applications of microbial electrochemical technologies (METs), such as bioenergy generation, environmental monitoring, resource recovery, and platform chemicals production, have been demonstrated. Despite these tremendous potentials, the scaling-up and commercialization of METs are still quite challenging. Depending on target applications, common challenges may include expensive and tedious fabrication processes, prolonged start-up times, complex design requirements and their scalability for large-scale systems. Incorporating the three-dimensional printing (3DP) technologies have recently emerged as an effective and highly promising method for fabricating METs to demonstrate power generation and biosensing at the bench scale. Notably, low-cost and rapid fabrication of complex and miniaturized designs of METs was achieved, which is not feasible using the traditional methods. Utilizing 3DP showed tremendous potentials to aid the optimization of functional large-scale METs, which are essential for scaling-up purposes. Moreover, 3D-printed bioanode could provide rapid start-up in the current generation from METs without any time lags. Despite numerous review articles published on different scientific and applied aspects of METs, as per the authors’ knowledge, no published review articles explicitly highlighted the applicability and potential of 3DP for developing METs. Hence, this review targets to provide a current overview and status of 3DP applications for advancing METs and their future outlook.